2005
DOI: 10.5713/ajas.2005.1701
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Phosphoinositide-3-kinase, Class 3 (PIK3C3) Gene and Association Tests with Quantitative Traits in Pigs

Abstract: This study deals with the characterization of porcine PIK3C3 and association tests with quantitative traits. PIK3C3 belongs to the class 3 PI3Ks that participate in the regulation of hepatic glucose output, glycogen synthase, and antilipolysis in typical insulin target cells such as those in the such as liver, muscle system, and fat. On the analysis of full-length mRNA sequence, the length of the PIK3C3 CDS was recorded as 2,664 bps. As well, nucleotide and amino acid identities between human and pig subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The T and C allele frequencies were 32.1% and 67.9%, and the T/T, C/T and C/C allele frequencies were 7.4%, 49.3% and 43.3%, respectively. Kim et al . (2005b) reported that the C allele frequency was 72.5% in 20 Duroc pigs, and there was no difference between their results and those obtained in this study ( χ 2 = 0.374, df = 1, P = 0.541).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The T and C allele frequencies were 32.1% and 67.9%, and the T/T, C/T and C/C allele frequencies were 7.4%, 49.3% and 43.3%, respectively. Kim et al . (2005b) reported that the C allele frequency was 72.5% in 20 Duroc pigs, and there was no difference between their results and those obtained in this study ( χ 2 = 0.374, df = 1, P = 0.541).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al . (2005b) sequenced full‐length porcine PIK3C3 complementary DNA (cDNA) and found five single nucleotide polymorphisms (SNPs) (C339G, C1401T, A2058G, A2256G and C2604T; the number indicates the position of the SNP in the PIK3C3 cDNA coding region) between Korean native and Large White pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(), and Kim et al . (), respectively (Table ). To genotype the LEPR polymorphism c.2002C>T in exon14, we developed a novel miss‐match PCR–RFLP method using miss‐match PCR primers (forward on exon 14 and reverse on intron 14) from the S. scrofa Ensembl genomic database (Sscrofa10.2; Ensembl gene ID, NW_003540913).…”
Section: Methodsmentioning
confidence: 96%
“…In the present study, we selected previously reported polymorphisms of five loci: leptin ( LEP ) at 21.201 Mb on SSC18 in the Ensembl genome browser 70: Sus scrofa comparative genomic database (Sscrofa10.2; http://www.ncbi.nlm.nih.gov/gene/396832), leptin receptor ( LEPR ) on SSC 6 (positional data has not yet been added to Sscrofa10.2), melanocortin 4 receptor ( MC4R ) at 178.553 Mb on SSC1 in Sscrofa10.2 (http://www.ncbi.nlm.nih.gov/gene/397359), class 3 phosphoinositide 3‐kinase ( PIK3C3 ) at 117.948 Mb on SSC 6 in Sscrofa10.2 (http://www.ncbi.nlm.nih.gov/gene/503700), and vertnin ( VRTN ) at 103.458 Mb on SSC7 in Sscrofa10.2 (http://www.ncbi.nlm.nih.gov/gene/100157734), which reportedly have significant effects on pig production traits (Kim et al . , ; Kennes et al . ; Chen et al .…”
Section: Introductionmentioning
confidence: 99%